Transposable Elements in Fungi: A Genomic Approach - Mateus F. Santana; Marisa V. Queiroz (Scientific Journal of Genetics and Gene Therapy - Peertechz Publications, 2015)
Transposable elements (TEs) include a wide range of DNA sequences that can change positions in the genome. The accessibility of whole fungal genome sequences and analysis of TEs demonstrate the important role they play in genome evolution of fungi species. TE activity is a primary mechanism for high fitness, plasticity and adaptability in certain species of pathogenic fungi. Some of the deleterious effects of transposons may be due to ectopic recombination among transposons of the same family. To prevent possible damage caused by the transposons, some fungi possess TE-silencing mechanisms, for instance, RIP (Repeat Induced Pont mutation) and RNA silencing. In addition, TEs are efficient molecular markers due to their structure and transposition strategy.